Keterkaitan Kepemimpinan Dan Kompensasi Dengan Prestasi Kerja Karyawan Pada Pt. Multi Informatika Solusindo - Mohammad Luqman Hakim dan Muhammad Halilintar (Jurnal Manajemen FE-UB, 2017)
Supervision is a very important activity in the implementation process of employee work. Control is essentially a process of organizing activities in accordance with the requirements specified in the plan. Implementation of effective supervision will give a better impact on employee performance. Job performance is basically what employees do or do not do. The purpose of this research is to know the implementation of supervision at the Head Office of PT. Multi Informatika Solusindo, to know employee performance at Head Office of PT. Multi Informatika Solusindo, and to know the impact of implementation of supervision on employee performance at Head Office of PT. Multi Informatika Solusindo. The method used in this research is descriptive with quantitative approach. Data collection techniques used interviews, observation, questionnaires and documentation. Analysis method using regression, pearson correlation and coefficient of determination, and t test by using the help of program SPSS 13.0 for windows. The survey took 81 respondents with error rate of 10%. The results of the research based on the responses of respondents mentioned that the implementation of supervision is on good criteria, and employee performance shows good criteria. Based on the results of the analysis, it can be seen that the level of relationship between the implementation of supervision and employee performance shows both variables are strong and unidirectional. The impact of the implementation of supervision on employee performance resulted 52.3%, while the remaining 47.7% influenced by other factors. Thus, the better the supervision performed by the company, will have a good impact on employee performance at the Head Office of PT. Multi Informatika Solusindo. Keywords: Supervision, Job Performance Employees, PT. Multi Informatika Solusindo.